Influence of Human, Livestock Population and Land use Systems on Soil Characteristics and Soil Organic Carbon Stock in Western Rajasthan - Singh, G; Nagora, P R; Mishara, Deepak; Hakasr, Parul; Gola, Sneha; Dandapath, Taipy (Annals of Arid Zone, 2019)
A study has been conducted during 2016-17 to estimate soil organic carbon stock in 0-30 cm soil depth as influenced by land use, spatial variations and human and livestock population for developing strategies to reduce land degradation and enhance carbon sequestration and land productivity. Forests, oran, pasture lands, agriculture, roadside and fallow land are different land uses covered in six Panchayat Samitis-called blocks viz. Abu Road, Baap, Baitu, Bali, Sanchor and Sankara situated in Sirohi, Jodhpur, Barmer, Pali, Jalore and Jaisalmer district, respectively in western Rajasthan. Land holding (2444-37444 m2), family size and livestock population in terms of head counts per household (HH-1; 5.3-5.9 and 4.4-11.0, respectively) varied (P<0.05) widely between blocks. Variations in soil gravel content, bulk density (BD), organic carbon (SOC) and carbon stock without (CSW) and with (CSG) gravel correction like 1.49-32.51%, 1.45-1.56 g cm-3, 0.114-0.584%, 5.31-25.37 t ha-1 and 5.04-16.63 t ha-1 between blocks, and 4.41-18.88%, 1.48-1.53 g cm-3, 0.133-0.324%, 6.08-14.20 and 5.73-9.72 t ha-1 respectively between land uses indicated strong spatial rather than land use effects. Spatial variation in annual rainfall and soil characteristics lead carbon stock in order: Baitu<Baap<Sankara<Sanchor <Bali<Abu Road among blocks, whereas overgrazing, organic manuring and vegetation status controlled land use order like roadside<fallow land<pastureland<agriculture<or an<forest land. Though varied between blocks and land uses, non-significant decrease in gravel and increase in BD during 2013 to 2017 indicated increased soil compactness. Thus increased rainfall/soil water and vegetation status favored soil carbon storage. Enhanced vegetation in forest, oran and pastureland, organic manuring of agriculture and avoiding overgrazing of pasture/rangelands can promote soil carbon sequestration and reverse the process of land degradation and improve land productivity. Key words: Carbon stock, land use, soil properties, spatial variations.